The glutathione biosynthesis in the psychrophile Pseudoalteromonas haloplanktis - ALBINO, ANTONELLA; MARCO, SALVATORE; DE VENDITTIS, EMMANUELE; MASULLO, MARIOROSARIO (2011)
Glutathione (GSH) plays a relevant role in the control of redox homeostasis even in philogenetically distant microbial species. The presence of GSH was recently hypothesized even in cold-adapted sources, on the basis of the effects produced by this thiol on some antioxidant enzymes from Pseudoalteromonas haloplanktis, a psychrophile isolated from the Antarctic sea. The possible existence of an enzyme system aimed at GSH biosynthesis in P. haloplanktis was investigated. This biochemical process involves the activity of the enzymes glutamyl-cysteine ligase (GshA) and glutathione synthetase (GshB). In the genome of P. haloplanktis two putative genes encoding GshA (PhGshAI and PhGshAII) and one encoding GshB (PhGshB) were identified. In order to characterize the first enzyme system for GSH biosynthesis in a psychrophilic source, recombinant forms of PhGshAII and PhGshB were obtained. It is known that each step leading to GSH from glutamate, cysteine and glycine involves the hydrolysis of one ATP molecule. Therefore, a convenient assay for determining the activity of each enzyme was set up, using the radiolabelled compound [γ32P]ATP. Concerning rPhGshB, the pH optimum of the activity was between 7.5 and 7.8. The affinity for ATP in the temperature range 10-30°C was evaluated. rPhGshB showed a significant activity even at low temperatures, whereas the Km ranges between 0.14 and 0.25 mM in the 10-30°C temperature range. The kcat values were analysed through the Arrhenius equation and the calculated energy of activation was 77 kJ/mol, a value unusually high for a psychrophilic enzyme. The heat inactivation profile of rPhGshB allowed the determination of a half-life of 10 min at 50.5°C, a value high for a psychrophilic enzyme, although not unusual for antioxidant enzymes. The energy of activation related to the inactivation process was 208 kJ/mol, as usually found for psychrophilic enzymes. The research is now focused on the characterization of rPhGshAII.